Relevance of universities and university affiliated colleges of education B.Ed economics curriculum to secondary school economics in South-west Nigeria (2024)
The study examined relevance of Universities and University affiliated Colleges of Education B. Ed Economics curriculum, and adopted (QUAN+qual) explanatory concurrent mixed method research design. Hundred (100) teachers were sampled across South-west geo-political zone of Nigeria through random sampling technique. Two validated instruments were used to collect data namely: Economics Curricula Relevance Inventory (r = 0.89) and Focus Group Discussion Guide. Four research questions were raised and answered. The data obtained were analysed using percentage count and thematic qualitative analysis. The result revealed that majority of the courses in universities and university affiliated colleges of education B.Ed Economics curriculum are highly relevant in teaching secondary school Economics. Some of these topics are: ECN 101 (Principle of Economics) (77%), ECN 201 (Introduction to micro economics I) (51%), ECN 204 (Mathematics for Economics) (74%), ECN 402 (Comparative Economics System) (52%), ECN 406 (Taxation and Fiscal Policy) (60%), ECN 407 (Petroleum Economics) (75%). The participants were however of the opinion that the major short-coming of the training received is that they are not well exposed to mathematical aspect of economics because majority of the course facilitators are fond of using old methods. It is therefore recommended that: there should be periodic evaluation of the B.Ed. Economics curriculum to ensure the inclusion of the use of software in the teaching of new teaching methods and mathematical aspects of Economics to the teacher trainees, so as to improve their teaching as well as enhance the requirements for the 21st century education.